Aberrant DNA Methylation of SOCS1 Gene is Not Associated with Resistance to Imatinib Mesylate among Chronic Myeloid Leukemia Patients - Elias, Marjanu H.; Azlan, Husin; Baba, Abdul Aziz; Ankathil, Ravindran (Cardiovascular & Haematological Disorders - Drug Targets, 2018)
Background: In exploring the cause of Imatinib Mesylate (IM) resistance among Chronic Myeloid Leukemia (CML) patients who do not harbor BCR-ABL dependent mechanism, BCR-ABL independent pathways are the most probable pathways that should be explored. In BCR-ABL independent pathway, SOCS1 plays an important role as it helps in regulating optimal JAK/STAT activity. Objective: To identify the association of SOCS1 gene hypermethylation in mediating IM Resistance. Method: The SOCS1 promoter methylation level of 92 BCR-ABL non mutated IM resistant CML patients, 83 IM good response CML patients and 5 normal samples from healthy individuals were measured using Methylation Specific-High Resolution Melt (MS-HRM) analysis. Results: Both primers used to amplify promoter region from -333 to -223 and from -332 to -188 showed less than 10% methylation in all CML and normal samples. Consequently, there was no significant difference in SOCS1 promoter methylation level between IM resistant and IM good response patients. Conclusion: SOCS1 promoter methylation level is not suitable to be used as one of the biomarkers for predicting the possibility of acquiring resistance among CML patients treated with IM.
Keywords: methylation